2018
DOI: 10.3201/eid2408.180228
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Nongroupable Neisseria meningitidis Disease in Vaccinated Patient Receiving Eculizumab

Abstract: Patients receiving eculizumab have an increased risk for meningococcal disease, but most reported cases are attributable to encapsulated meningococcal strains. We describe a case in which a nongroupable meningococcal strain, which rarely causes disease in healthy persons, caused fatal disease in an eculizumab recipient despite meningococcal vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 13 publications
1
28
0
2
Order By: Relevance
“…Similarly, the terminal complement pathway inhibitor, eculizumab, which is used to treat paroxysmal nocturnal haemoglobinuria and atypical haemolytic uraemic syndrome, is associated with up to 2,000-fold increased incidence of invasive meningococcal disease. This includes disease caused by unencapsulated strains, such as the US_NmUC strain, that would not normally cause disease in healthy individuals [15]. These individuals are recommended to receive meningococcal vaccination and long-term penicillin prophylaxis [16].…”
Section: Implications Of the Emergence Of Meningococci Adapted To Thementioning
confidence: 99%
“…Similarly, the terminal complement pathway inhibitor, eculizumab, which is used to treat paroxysmal nocturnal haemoglobinuria and atypical haemolytic uraemic syndrome, is associated with up to 2,000-fold increased incidence of invasive meningococcal disease. This includes disease caused by unencapsulated strains, such as the US_NmUC strain, that would not normally cause disease in healthy individuals [15]. These individuals are recommended to receive meningococcal vaccination and long-term penicillin prophylaxis [16].…”
Section: Implications Of the Emergence Of Meningococci Adapted To Thementioning
confidence: 99%
“…Since eculizumab blocks the terminal complement pathway, which is required for serum bactericidal activity, patients treated with eculizumab are at more than a 1000‐fold increased risk of meningococcal disease . While no deaths were reported in the paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome studies, fatal infections have subsequently been reported . In the U.S., 52% of meningococcal disease are caused by serogroups A, C, Y or W‐135 and 48% by serogroup B.…”
Section: Eculizumabmentioning
confidence: 99%
“…in addition to the known risk of N. meningitidis disease. Further, recent data suggest that patients receiving eculizumab are at risk for meningococcal infections caused by nongroupable strains, which do not usually cause invasive disease in healthy people [16,24]. The patients in this series may be exhibiting a similar susceptibility to severe infection by species that rarely pose a risk for invasive infection in healthy individuals.…”
Section: Discussionmentioning
confidence: 77%